A KONSEP AKAD MUDHARABAH LINKAGE PROGRAM PADA LEMBAGA KEUANGAN SYARIAH: KONSEP AKAD MUDHARABAH LINKAGE PROGRAM PADA LEMBAGA KEUANGAN SYARIAH - Faiqotun Ni'mah Faiqotun Ni'mah (STAI AL-HIDAYAT Lasem, 2025)
Mudharabah contract is not only used by bank and non-bank financial institution to customer, but also used by commercial bank to microfinance institution with cooperation namely linkage program. Purpose of this research is to explain the islamic linkage program. Islamic linkage program is similar with conventional linkage program, the difference is the contract. In islamic linkage program, executing uses mudharabah contract, channeling uses wakalah contract, and joint financing uses musyarakah contract. This research focuses on discuss about mudharabah contract because the majority of islamic banking are use the mudharabah contract to channel their funds to microfinance institution.